2019
DOI: 10.32098/mltj.01.2018.21
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different fitting methods for in-vivo bi-component T2* analysis of human patellar tendon in magnetic resonance imaging

Abstract: Purpose: To investigate the robustness of four fitting methods for bi-component effective spin-spin T2 (T2*) relaxation time analysis of human patellar tendon. Methods: A three-dimensional (3D) cone ultrashort echo-time (UTE) sequence was performed on the knees of ten healthy volunteers at 3.0T. Four fitting methods incorporating either Gaussian or Rician noise distribution were used for voxel-by-voxel bi-component T2* analysis of the patellar tendon. The T2* for the short relaxing (T**,s) and long relaxing (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…However, our study and the study performed by Juras et al found no significant difference in T2*normalS between patients with tendinopathy and healthy volunteers. This may be the result of the increased uncertainty and higher sensitivity to noise of T2*normalS parameter estimation due to the relatively small fraction of the slow relaxing water component in tendon, which provides little MRI signal at later echoes …”
Section: Discussionmentioning
confidence: 55%
“…However, our study and the study performed by Juras et al found no significant difference in T2*normalS between patients with tendinopathy and healthy volunteers. This may be the result of the increased uncertainty and higher sensitivity to noise of T2*normalS parameter estimation due to the relatively small fraction of the slow relaxing water component in tendon, which provides little MRI signal at later echoes …”
Section: Discussionmentioning
confidence: 55%
“…We have demonstrated that the proposed 3D UTE‐Cones AFI‐VFA method can accurately measure T 1 values for most major tissues of the whole knee joint. Simulation shows that the proposed 3D UTE‐Cones AFI‐VFA method provides accurate T 1 measurements for tissues with T 2 values longer than 1 ms. Because most knee tissues have T 2 s longer than 1 ms (meniscus: 5–8 ms, ligament and tendon: 4–10 ms, cartilage: 27–43 ms, muscle: 32–50 ms, and fat: ~133 ms), accurate T 1 maps were obtained using the proposed method to provide in vivo knee measurements in 16 healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…An 8‐channel transmit–receive knee coil was used for both RF transmission and signal reception. Unique k‐space trajectories were used in the UTE‐Cones sequences that sampled data along evenly spaced twisted paths in the form of multiple cones . Data sampling began from the center of k‐space and continued outward.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, incorporation of Rician noise into CRLB analysis is especially important in settings of limited SNR, as is often the case in clinical imaging (11, 2326). …”
Section: Introductionmentioning
confidence: 99%